PULPOTOMÍA CON UN CEMENTO BIOCERÁMICO BIOACTIVO EN UN DIENTE PERMANENTE JOVEN CON TRAUMATISMO DENTAL: REPORTE DE CASO - Nieves Neira Valdez, Kruspkaya Sylvia (2025)
Objective: To describe the conservative clinical approach to an inmature permanent anterior tooth with traumatic pulp exposure treated total pulpotomy using a mineral-trioxide-aggregate-derived bioceramic cement (Neoputty), in order to maintain pulpal vitality and allow continued root development. Case report: A 9-year-9-month-old male patient  presented 72 hours after suffering dental trauma. The patient’s mother reported sensitivity to cold and pain during mastication. Intraoral examination revealed a complicated crown fracture with pulp exposure and tenderness to percussion affecting the upper left permanent central incisor (tooth 21). Radiographic assessment revealed the crown fracture with pulpal involvement, periodontal ligament widening and an open apex. A total pulpotomy was performed using a bioactive bioceramic material (NeoPutty), followed by clinical and radiographic follow-ups at 2, 5, and 8 months. The treated tooth remained asymptomatic, exhibited no discoloration, and demonstrated appropriate apical development. Conclusion: Total pulpotomy proved to be an effective conservative treatment option for a young permanent tooth with traumatic pulp exposure, preserving pulpal vitality and promoting physiological apexogenesis.